Fault Mapping of the Central Aceh Segment of the Sumatran Fault as an Extension of the Great Sumatran Fault (GSF) Using Gravity Analysis - Qisthi Mursyida; Muhamad Syirojudin (Yayasan Kita Menulis - JoCPES, 2025)
Aceh is known as one of the most tectonically active regions in Indonesia with a relatively high level of seismicity. One of the active zones is the Central Aceh Segment, which forms part of the Sumatra Fault as an extension of the Great Sumatran Fault. This study aims to identify the distribution and characteristics of fault zones and types in the Central Aceh Segment using gravity data from GGMplus. The analysis was carried out by applying the First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) methods. The results indicate significant lateral density contrasts that delineate the presence of a major fault and several secondary fault structures within the study area. Interpretation of SVD values along several profiles suggests that many of the inferred structures exhibit reverse fault characteristics, with some indications of normal faults. These features are interpreted as secondary deformation structures that may develop within a strike-slip fault under localized transpressional or transtensional stress regimes. Subsurface geological modelling along profiles AA′–BB′, BB′–CC′, and EE′–FF′ shows variations in rock density that highlight zones of high-density distribution.